2000
DOI: 10.3354/cr015151
|View full text |Cite
|
Sign up to set email alerts
|

Causes of variability in monthly Great Lakes water supplies and lake levels

Abstract: The purpose of this study was to identify those water budget components of the Great Lakes that have most frequently been a major cause of anomalous net basin supplies (NBS) and of rising and falling lake levels at the monthly time scale. Principal component analysis and a simple counting of relative frequencies revealed that on the upper lakes NBS anomalies are most sensitive to overlake precipitation, but on the lower lakes they are most sensitive to runoff. This shift is due to a downstream increase in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…An early spring thaw leads to a late winter freeze-up, creating a positive feedback loop [1,36]. Studies have shown that changing climate has resulted in decreased ice cover over the Great Lakes [4,[37][38][39][40]. Now, this study is also finding that the changes in the ice cover themselves have an impact on the Great Lakes' hydro-climate and thermal stratification as a whole.…”
Section: Interannual Variationmentioning
confidence: 53%
“…An early spring thaw leads to a late winter freeze-up, creating a positive feedback loop [1,36]. Studies have shown that changing climate has resulted in decreased ice cover over the Great Lakes [4,[37][38][39][40]. Now, this study is also finding that the changes in the ice cover themselves have an impact on the Great Lakes' hydro-climate and thermal stratification as a whole.…”
Section: Interannual Variationmentioning
confidence: 53%
“…It was recently determined that long‐term lake level fluctuations were primarily resulting from changes in precipitation [ Brinkmann , 2000; Hanrahan et al , 2009], and since the pre‐1980 interannual variation of evaporation was relatively small, it had little effect on long‐term lake level variations. Over the last few decades however, evaporation rates have begun to increase, resulting in decreasing lake levels despite continued above‐average precipitation totals.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…a2. Probability Density Function (PDF) of time intervals between consecutive lakelevel maxima based on ridge data for Baileys Harbor only (Thompson and Baedke, 1997, 2000 (solid black line). Dashed lines show the 95% confidence interval associated with red-noise null hypothesis (see text).…”
Section: Appendix a Paleodata Analysismentioning
confidence: 99%